Políticas urbanas para o espaço global - Tamara Tania Cohen Egler (El Colegio Mexiquense, A.C., 2005)
This paper shows the fact that we are undergoing a transition process created by the new information and communication technologies that transform the spatial processes. Its configuration is the result of having fragmented cities in different places of the world, which are connected by informational fluxes of technological support that get articulated to relate the place with the global fluxes and create a new spatial totality without a scale. We propose to examine how the urban policies in Brazil are getting more associated with the production of localised interventions, in the sense of connecting the ports of our cities with the global space. In order to achieve our task, we start by examining the new forms of the global space, the logics and planning of the urban policies and the effects in the social space to unravel the power to destroy the communities of the place and redefine the social use of space in benefit of the interest of the globalised elites.